Synthesis, microstructure and biodegradation behavior of nano-Si and nano-ZnO/Si coatings on a Mg/HA/TiO2/MgO nanocomposite - Khalajabadi, Shahrouz Zamani (Taylor and Francis Inc., 2015)
In this study, a successful synthesis of nano-Si single-layer and nano-ZnO/Si double-layer coatings on Mg/HA/TiO2/MgO nanocomposite using radio frequency magnetron sputtering was investigated by X-ray diffraction, X-ray photoelectron spectroscopy, field-emission scanning electron microscopy, transmission electron microscopy and atomic force microscopy. The double-layered ZnO/Si nano-composite coating consisted of ZnO nanospheres with an average particle size of 28 nm as the outer layer (~0.6-µm-thick, sputtering pressure of 0.16 Pa) and the columnar microstructure of Si with an average particle size of 32 nm in length and 21 nm in width as the inner layer (~1.1-µm-thick, sputtering pressure of 0.24 Pa). Microstructural analysis reveals little surface damage after ZnO/Si coatings initially and after 168 h immersion in simulated body fluid, corrosion protective products including Mg(OH)2, Ca10(PO4)6(OH)2 and carbonate ions are formed on the uncoated and coated samples. A significant increase in the corrosion resistance (~2.55 kO cm2) of the nano-ZnO/Si-coated sample was observed in simulated body fluid compared to the Si-only coated samples (~2.17 kO cm2) and the uncoated samples (~0.14 kO cm2). Hydrogen evolution studies showed that the nano-ZnO/Si-coated sample (1.07 ml/cm2/day) had a lower degradation rate than the Si-only coated sample (2.17 ml/cm2/day) and uncoated sample (4.42 ml/cm2/day).